Retrospective study of online ligation student practice incorporating flipped learning into e-learning - Okada, Takuhisa; Asao, Takayuki; Inoue, Hitoshi; Harimoto, Norifumi; Tanaka, Kazumi; Shiraishi, Takuya; Sano, Akihiko; Ogawa, Hiroomi; Sohda, Makoto; Shirabe, Ken; Saeki, Hiroshi (Surgery today (Tokyo, Japan), 2022)
Purpose Flipped learning has been applied in various fields, including medical professional education. E-learning is compatible with flipped learning; however, it is considered to be unsuitable for providing training on surgical techniques. In this study, we retrospectively examined the ligation performance of online students who underwent training with flipped learning incorporated into e-learning. Methods We conducted a retrospective study of the ligation practices of online students at the Department of General Surgery from March 2020 to June 2021. The subjects included 134 fourth- and fifth-year medical students from Gunma University School of Medicine. We conducted mid-term checks on the 8th day of practice and an examination on the 19th day. Two instructors independently evaluated and calculated scores using the original Global Rating Scale of Gunma University. We also conducted a questionnaire survey on the ligation practice of online students. Results The total average score of the three tasks was 12.4 for Instructor 1 and 12.0 for Instructor 2. All students had a passing score. The questionnaire survey showed that 70% of the students were trained in ligation at the time of the first evaluation. Conclusions Our online training materials and training methods enabled the acquisition of ligation skills by students who had not previously received ligation training.